Behandlungsqualität des Diabetes mellitus und Inzidenz schwerer Hypoglykämien in stationären und ambulanten Versorgungseinrichtungen: Heidelberger Diabetesstudie = Diabetes care and incidence of severe hypoglycemia in nursing home facilities and nursing services : the Heidelberg diabetes study - Bahrmann, Anke; Wörz, Eva; Specht-Leible, Norbert; Oster, Peter (Zeitschrift für Gerontologie und Geriatrie, 2015)
AimThe goal of this study was to perform a structured analysis of the treatment quality and acute complications of geriatric patients with diabetes mellitus (DM) cared for by nursing services and nursing home facilities. Secondly, structural problems and potentials for improvement in the care of multimorbid older people with DM treated by nursing homes and nursing services were analysed from the viewpoint of geriatric nurses, managers of nursing homes and general practitioners.MethodsIn all, 77 older persons with DM from 13 nursing homes and 3 nursing services were included in the analysis (76.6 % female, HbA1c 6.9 ± 1.4 %, age 81.6 ± 9.9 years). Structural problems and potentials for improvement were collected from 95 geriatric nurses, 9 managers of nursing homes and 6 general practitioners using semistandardized questionnaires.ResultsMetabolic control was too strict in care-dependent older people with DM (mean HbA1c value: 6.9 ± 1.4 %; recommended by guidelines: 7-8 %). The measurement of HbA1c was performed in 16 of 77 people (20.8 %) within the last year despite a high visitation frequency of the general practitioners (12.7 ± 7.7 within the last 6 months). The incidence of severe hypoglycemia was 7.8 %/patient/year. Regarding the management in case of diabetes-related acute complications 33 geriatric nurses (34.7 %) stated not having any written standard (nursing home 39 %, geriatric services 16.7 %).ConclusionComplex insulin therapies are still used in older people with DM with the consequence of a high incidence of severe hypoglycemia. Concrete management standards in the case of diabetes-related acute complications for geriatric nurses are lacking for more than one third of the nursing services.